Contingent loan repayment in the Philippines - Fafchamps, M; Gubert, F (University of Oxford, 2004)
Using data from the Philippines, this paper seeks to understand how households in the study area apparently manage to avoid falling in a debt trap in spite of frequent borrowing. Findings suggest this is achieved via three institutional features. First, most informal debt carries no interest. As we show in the conceptual section, charging zero interest makes a debt trap impossible. Second, for all debts, repayment is postponed in case of borrower's difficulty; this is the only insurance feature of debt repayment. Third, while debt principal is seldom forgiven or reduced, interest-bearing debt does not carry additional interest if debt repayment is delayed. This prevents interest charges from accumulating and debt from snowballing.